Factors Influencing Client Loyalty in a Tax Consultant Office: Faktor-faktor yang Mempengaruhi Loyalitas Klien di Kantor Konsultan Pajak. - Melinda Rofiatul Adhaniyah; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to investigate the influence of relationship quality, service quality, perceived value, and trust on client loyalty in a tax consultant office. The population of this study was 101, and the sample size was 38, selected using nonprobability sampling with the accidental sampling method. Multiple linear regression analysis was used to analyze the data with SPSS version 26. The results showed that relationship quality, service quality, perceived value, and trust had a significant positive effect on client loyalty. The findings of this study have implications for tax consultant offices to improve their relationship quality, service quality, perceived value, and trust to enhance client loyalty. Highlights: The study examines the impact of multiple factors on client loyalty in a tax consultant office. The sample size of 38 was selected using nonprobability sampling with the accidental sampling method. The findings suggest that improving relationship quality, service quality, perceived value, and trust can enhance client loyalty in tax consultant offices. Keywords: relationship quality, service quality, perceived value, trust, client loyalty